The Effect of Smart Grid Implementation on the Integration of New Renewable Energy in Indonesia's Electricity System - Judijanto, Loso; A, Sulaiman; Tahir, Usman (West Science Nature and Technology, 2024)
This study examines the effect of smart grid implementation on the integration of new renewable energy (NRE) in the Indonesian electricity system from the consumer's perspective. Using a qualitative approach, data were collected through interviews with five informants and analyzed with NVIVO software. The findings reveal that smart grids enhance renewable energy integration by improving energy efficiency, consumer participation, and environmental sustainability. However, challenges such as infrastructure readiness, affordability, and limited consumer awareness hinder adoption. Informants emphasized the need for government support, subsidies, and public education to accelerate implementation. This research highlights the critical role of consumers in achieving Indonesia's renewable energy targets and offers recommendations for stakeholders to foster a consumer-centric approach to smart grid deployment.